2016
DOI: 10.1038/srep21387
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening hydrogels for investigating the dynamics of hepatic stellate cell mechanotransduction during myofibroblast activation

Abstract: Tissue fibrosis contributes to nearly half of all deaths in the developed world and is characterized by progressive matrix stiffening. Despite this, nearly all in vitro disease models are mechanically static. Here, we used visible light-mediated stiffening hydrogels to investigate cell mechanotransduction in a disease-relevant system. Primary hepatic stellate cell-seeded hydrogels stiffened in situ at later time points (following a recovery phase post-isolation) displayed accelerated signaling kinetics of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(209 citation statements)
references
References 45 publications
10
199
0
Order By: Relevance
“…Differentiation of HSCs into myofibroblasts has been closely related to tissue fibrosis, which might be partially attributed to ECM stiffening during disease development. Their results confirmed that HSCs cultured on stiffer hydrogels (~24 kPa in elasticity) expressed higher levels of alpha-smooth muscle actin (α-SMA) and type I collagen, as compared to HSCs on softer hydrogels (~2 kPa) [255, 257]. These results suggest that the dynamic nature of such hydrogels could be leveraged to study biological processes related to ECM stiffening in vitro ; a feat that is not easily be achieved in traditional static hydrogels.…”
Section: Temporal Control Of Hydrogelmentioning
confidence: 75%
See 2 more Smart Citations
“…Differentiation of HSCs into myofibroblasts has been closely related to tissue fibrosis, which might be partially attributed to ECM stiffening during disease development. Their results confirmed that HSCs cultured on stiffer hydrogels (~24 kPa in elasticity) expressed higher levels of alpha-smooth muscle actin (α-SMA) and type I collagen, as compared to HSCs on softer hydrogels (~2 kPa) [255, 257]. These results suggest that the dynamic nature of such hydrogels could be leveraged to study biological processes related to ECM stiffening in vitro ; a feat that is not easily be achieved in traditional static hydrogels.…”
Section: Temporal Control Of Hydrogelmentioning
confidence: 75%
“…Importantly, the degree of photopolymerization reaction is dependent on the light irradiation dose [251]. As a result, it is possible to take advantage of the dose-dependent crosslinking density, which leaves unreacted functional groups within the hydrogel matrix, which can be subsequently crosslinked in a second step to increase mechanical strengths at a time point of choice [251257]. …”
Section: Temporal Control Of Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experiments showed that HSCs seeded on soft substrates remained quiescence with lipid droplets, whereas stellate cells cultured on stiff substrates remained activated while losing their lipid droplets. Meanwhile, stellate cells initially cultured on soft gels, subjected to secondary cross-linking responded rapidly to the change in substrate stiffness, resembling the myofibroblast-like morphology, which indicates that there is a positive feedback between fibrosis and LSECs capillarization [57] .…”
Section: Activation To Fibrosis and Induced Differentiation Of Hsc Acmentioning
confidence: 99%
“…Stiffening HA substrates were used to mimic fibrosis and consequent myofibroblast activation in hepatic stellate cells. [95] Anseth and colleagues extended this work to cellladen 3D hydrogels using PEG-based hydrogels to investigate microenvironmental stiffening on valvular interstitial cell (VIC) activation. [96] VIC embedded in soft gels (0.24 kPa) exhibited a myofibroblast phenotype, while upon stiffening (to 1.2 or 13 kPa) via a photoinitiated thiol-ene polymerization, they reverted to a quiescent, fibroblast phenotype, irrespective of cell morphology.…”
Section: Time-dependent Matrix Stiffeningmentioning
confidence: 99%